Near-surface dynamics of a gas bubble collapsing above a crevice. (25th September 2020) - Trummler, Theresa; Bryngelson, Spencer H.; Schmidmayer, Kevin; Schmidt, Steffen J.; Colonius, Tim; Adams, Nikolaus A.
Abstract: Abstract : The impact of a collapsing gas bubble above rigid, notched walls is considered. Such surface crevices and imperfections often function as bubble nucleation sites, and thus have a direct relation to cavitation-induced erosion and damage structures. A generic configuration is investigated numerically using a second-order accurate compressible multi-component flow solver in a two-dimensional axisymmetric coordinate system. Results show that the crevice geometry has a significant effect on the collapse dynamics, jet formation, subsequent wave dynamics and interactions. The wall-pressure distribution associated with erosion potential is a direct consequence of development and intensity of these flow phenomena.